Comparative study on molecular size, multi‐branched structure, and chain conformation of amylopectins from three rice cultivars. Issue 9 (26th May 2014) - Hu, Ting; Zhao, Siming; Huang, Qilin
<x xml:space="preserve">Abstract</x> Molecular size, multi‐branched structure, and chain conformation of amylopectins from indica (Ir‐AP), japonica (Jr‐AP), and glutinous rice (Gr‐AP) were investigated by laser light scattering (LLS), isoamylase debranching with gel permeation chromatography (GPC) separation and viscometry. The weight‐average molecular weight (Mw), radius of gyration (〈S2〉1/2), and intrinsic viscosities ([η]) in DMSO at 25°C were measured separately for Ir‐AP (4.72 ± 0.15 × 107, 163.70 ± 2.1 nm and 456.47 mL/g), Jr‐AP (6.61 ± 0.41 × 107, 170.40 ± 2.6 nm and 569.68 mL/g), and Gr‐AP (2.35 ± 0.34 × 108, 253.20 ± 16.3 nm and 926.08 mL/g). The Gr‐AP showed a dramatically lower overlapping concentration (c* = 1/(A2Mw), 1.40 × 10−4 g/mL) than Ir‐AP and Jr‐AP (1.13 × 10−3 g/mL and 1.04 × 10−3 g/mL), indicating that the first had more entanglements between macromolecular chains than the latter two. Based on the cluster model and A:B chain ratios, the Gr‐AP had more branched chains and longer internal‐chains than Ir‐AP and Jr‐AP. In view of polymer solution theory, the molecular parameters of ρ (viscometric radius Rη/〈S2〉1/2) and σ (A2Mw/[η]) revealed that Ir‐AP, Jr‐AP, and Gr‐AP existed as hyperbranched chains occupying a spherical volume and the first two presented a star‐like branched conformation in DMSO. This research provides the insights into multi‐branched structure and chain conformation of AP as well as a theoretical basis for interpretation of AP functional properties associated with their molecular structure.